1988
DOI: 10.1002/ardp.19883210204
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Assay of 5,5′‐(Salicylidene)bis‐(2‐thiobarbituric acid)

Abstract: The spectrophotometric assay of 5,5'-(salicylidene)bis-(2-thiobarbituric acid), which shows interesting pharmacological perspectives, is proposed, Spektrornetrische Bestimmung der 5,5'-(Salicyliden)bis-(2-thiobarbitursaure) applying the conventional and differential photometries. The conventional photometry is developed at pH 4.00 (NaOAc-HOAc buffer). The differential photometry is realized for two series of pH (pH 10.5/13.5 and pH 2.0/10.5). A comparative study between the different photometries indicates a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The 250 C peak for the Mn II complex is due to dehydration of the coordinated water. The peaks at 188.2, 272 and 280.4 C for copper and manganese complexes, respectively, are probably due to 3 ] Á 5H 2 O complexes gave seven and eight peaks, respectively. The ®rst two peaks at 92.6 and 131.6 C for the cobalt complex and 85.5 and 151.0 C for the nickel complex are due to dehydration of the outer sphere water molecules.…”
Section: Dta Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…The 250 C peak for the Mn II complex is due to dehydration of the coordinated water. The peaks at 188.2, 272 and 280.4 C for copper and manganese complexes, respectively, are probably due to 3 ] Á 5H 2 O complexes gave seven and eight peaks, respectively. The ®rst two peaks at 92.6 and 131.6 C for the cobalt complex and 85.5 and 151.0 C for the nickel complex are due to dehydration of the outer sphere water molecules.…”
Section: Dta Analysismentioning
confidence: 95%
“…Most pyrimidines have antimicrobial, anti-in¯ammatory and antitumor properties [2,3]. Masoud et al 5-Nitrobarbituric acid was reported for the identi®cation of 4-aminopyridine by microcrystal reaction [45].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, barbituric acid and its simple C5-substituted derivates have found numerous applications in medicinal chemistry. Barbituric acid, formally a cyclic urea derivative, is of particular interest in view of its pharmacological, biochemical, and biological capabilities. For example, the thymine group of deoxyribonucleic acid (DNA) gives barbituric acid upon biological oxidation . In the present study, 5-nitrobarbituric acid (also named dilituric acid or 5-nitro-2,4,6-trihydroxypyrimidine) is selected as a structural component instead of barbituric acid because the presence of the nitro group provides additional hydrogen-bonding acceptor sites for supramolecular assembly of the host lattice.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic applications of thiobarbituric acid are reported [3]. Most of the pyrimidines are with antimicrobial, anti-inflammatory, and antitumoral activities properties [2,4].…”
Section: Introductionmentioning
confidence: 99%